Quality of life and psychological aspects in children with overactive bladder treated with parasacral transcutaneous electrical nerve stimulation - A prospective multicenter study. Issue 6 (December 2022) - Leão S Santos, Herbert; Caldwell, Patrina; Hussong, Justine; von Gontard, Alexander; Estevam de Abreu, Glicia; Braga, Ana Aparecida; Veiga, Maria Luiza; Hamilton, Sana; Deshpande, Aniruddh; Barroso, Ubirajara
Summary: Objective: To assess the impact of parasacral transcutaneous electrical nerve stimulation (parasacral TENS) on quality of life (QoL) and psychological aspects in children treated for overactive bladder (OAB). Methods: This international, multicenter, prospective cohort study involved individuals of 6–16 years of age under TENS treatment for OAB. The study was conducted between June 2016 and December 2019 in four participating centers: two in Australia, one in Germany and one in Brazil. Patients with anatomical and/or neurological abnormalities of the urinary tract were excluded. Questionnaires were applied before and after parasacral TENS treatment: the Dysfunctional Voiding Symptom Score (DVSS), used in Brazil, or the International Consultation on Incontinence Questionnaire - Pediatric Lower Urinary Tract Symptoms (ICIQ-CLUTS), used in Germany and Australia, to analyze urinary symptoms; the Strengths and Difficulties Questionnaire (SDQ) to assess emotional and behavioral aspects; and the Pediatric Incontinence Questionnaire (PinQ) for bladder-specific Qol. Results: Fifty-three patients (28 girls and 25 boys) with a mean age of 8.64 ± 2.63 years were included. Median DVSS was 11 (range 6–13.5) and 3 (range 0–7), (p < 0.001), and median ICIQ-CLUTS was 12 (range 9–14) and 9 (range 5.7–12), (p < 0.001), before and after treatment, respectively. Median PinQ score decreased from 47.8 (range 38.9–59.7) to 39 (range 29–53.15) following treatment (p = 0.04). Median total SDQ score before and after treatment was 17 (range 13.5–21) and 15 (range 12–21), respectively (p = 0.939). Conclusion: Parasacral TENS was associated with a significant improvement in urinary symptoms and QoL; however, there was no change in psychological symptoms, as measured using the SDQ. Summary Table Comparison of quality of life (PinQ) scores before and after treatment with Parasacral TENS. Summary Table Analyze M (IR) PinQ p∗-value N Baseline End of Treatment Total sample           47.8 (38.9–59.7) 39 (29–53.15) 0.04 37 Questionnaire; M = Median; IR = Interquartile range; N = number of patients.